Psychosocial Work Environment Among Musicians and in the General Workforce in Norway - Détári, Anna; Egermann, Hauke; Bjerkeset, Ottar; Vaag, Jonas (Frontiers in Psychology, 2020)
Musicians suffer from physical and mental symptoms more frequently than the general population. Although their specific demands and challenges have been researched increasingly in the past, explanations still remain somewhat unclear. We use a large epidemiological data set to compare psychosocial work environment among 1607 members of the Norwegian Musician’s Union with 4168 employees from the general Norwegian workforce, using the QPS-Nordic scale and the Job Content Questionnaire (JCQ). Musicians reported more control over their work, however, felt less supported and acknowledged, had more family-work conflicts and less motivation, and perceived their work as more demanding compared to the general workforce. In the musician sample, results indicated that classical and contemporary musicians are experiencing a less favourable psychosocial environment in terms of control, demands, and acknowledgement, orchestral players felt less control and soloist less support. Future studies should explore possible interventions to improve musicians’ psychosocial work environment.